2022
DOI: 10.1093/plphys/kiac447
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid modulates neighbor proximity-induced leaf hyponasty in Arabidopsis

Abstract: Leaves of shade-avoiding plants such as Arabidopsis (Arabidopsis thaliana) change their growth pattern and position in response to low red to far-red ratios (LRFRs) encountered in dense plant communities. Under LRFR, transcription factors of the phytochrome interacting factor (PIF) family are de-repressed. PIFs induce auxin production, which is required for promoting leaf hyponasty, thereby favoring access to unfiltered sunlight. Abscisic acid (ABA) has also been implicated in the control of leaf hyponasty, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…One possibility is that Striga maintains hyperactive phytochromes consistent with the phenotypes of PHYA over-expressors (FRANKLIN and WHITELAM, 2005). Interestingly, it was recently shown that ABA modulates shade avoidance by inducing hyponasty movement in Arabidopsis (Michaud et al, 2022) adding to another piece of circumstantial evidence for ABA involvement in Striga ’s germination and infection process. This is an interesting subject for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that Striga maintains hyperactive phytochromes consistent with the phenotypes of PHYA over-expressors (FRANKLIN and WHITELAM, 2005). Interestingly, it was recently shown that ABA modulates shade avoidance by inducing hyponasty movement in Arabidopsis (Michaud et al, 2022) adding to another piece of circumstantial evidence for ABA involvement in Striga ’s germination and infection process. This is an interesting subject for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Next, auxin signaling in the lower side of the petiole stimulates local gibberellic acid (GA) biosynthesis, initiating abaxial cell elongation, and hence petiole hyponasty (Küpers et al, 2022). Concomitantly, abscisic acid (ABA) signaling stimulates hyponasty, potentially through the interaction with sugar signaling (Michaud et al, 2022). Much of the SAS-related hormonal crosstalk is shared with thermonastic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pivotal function of auxin in regulating LRFR-induced hyponasty has been well-studied (Michaud et al, 2017;Pantazopoulou et al, 2017), knowledge on the role of other phytohormones in this phenomenon is scarce. In this issue of Plant Physiology, Michaud et al (2022) report that abscisic acid (ABA) plays a crucial role in mediating LRFR-induced hyponasty. They demonstrate that exposure to LRFR rapidly increases the biosynthesis of ABA, which is necessary for the upward movement of leaves in the proximity of competing neighbors.…”
mentioning
confidence: 99%
“…LRFR induces auxin production in the leaf blade, which ultimately mediates the hyponastic leaf movement (Michaud et al, 2017). Considering this, Michaud et al (2022) compared leaf movements of WT and aba2 after exogenous application of auxin (Indole-3-acetic acid, IAA) to their leaf tips. The aba2 mutant exhibited a reduced hyponastic response compared to WT upon IAA application, indicating that auxin-induced leaf movements require ABA biosynthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation